Functionalized Cyclopropanes as Versatile Intermediates for the Diversity-Oriented Synthesis of γ-Lactones, γ-Lactams and δ-Lactams - Maximiano, Adrielle P.; Ramos, Giovana S.; Marques, Marcelo V.; Sá, Marcus M. (Synthesis, 2021)
A two-step procedure for the preparation of cyclopropanecarboxaldehyde-1,1-diester from a γ,δ-epoxyester and its synthetic versatility are described herein. The epoxide ring-opening/cyclopropanation process occurs in the presence of Mg(ClO4)2 under heating, resulting in cyclopropanemethanol-1,1-diester in 65% yield. A mild TEMPO-mediated oxidation of this substrate readily generated the corresponding aldehyde in 75% yield, which was applied in the one-pot synthesis of four cyclopropylidene-γ-lactams and three δ-lactams. In addition, vinylcyclopropanes were obtained through the Wittig reaction of the aldehyde with phosphonium salts and used as precursors for tetrahydrofurans.
Keywords: γ,δ-epoxyester; cyclopropanecarboxaldehyde; lactonization; cyclopropylidene-γ-lactams; δ-lactams; one-pot process; structural diversity